Differential Ascending Projections From the Male Rat Caudal Nucleus of the Tractus Solitarius: An Interface Between Local Microcircuits and Global Macrocircuits - Kawai, Yoshinori (Frontiers in Neuroanatomy, 2018)
To integrate and broadcast neural information, local microcircuits and global macrocircuits interact within certain specific nuclei of the central nervous system. The structural and functional architecture of this interaction was determined for the caudal nucleus of the tractus solitarius (NTS) at the level of the area postrema, a relay station of peripheral viscerosensory information that is processed and conveyed to brain regions concerned with autonomic-affective and other interoceptive reflexive functions. Axon collaterals of most small NTS cells (soma < 150 µm2) establish excitatory or inhibitory local microcircuits likely to control the activity of nearby NTS cells and to transfer peripheral signals to efferent projection neurons. At least two types of cells that constitute efferent pathways from the caudal NTS were distinguished: (1) a greater numbers of small cells, seemingly forming local excitatory microcircuits via recurrent axon collaterals, that project specifically and unidirectionally to the lateral parabrachial nucleus, and (2) a much smaller numbers of cells likely to establish multiple global connections, mostly via the medial forebrain bundle or the dorsal longitudinal fascicle, with a wide range of brain regions, including the ventrolateral medulla, hypothalamus, central nucleus of the amygdala, bed nucleus of the stria terminalis, spinal cord dorsal horn, brainstem reticular formation, locus coeruleus, periaqueductal gray, and periventricular diencephalon (including the epithalamus). The evidence presented here suggests that distinct caudal NTS cell types distinguished by projection pattern and related structural and functional features participate differentially in the computation of viscerosensory information and coordination of global macro-networks in a highly organized manner.